Faría, la educación colombiana y nortesantandereana (2021)
Talking about education today reveals nothing new for a knowledge society that has a thousand entries on the same topic. However, this paper will attempt to reconstruct what the philosopher and thinker from Norte de Santander José Rafael Faría Bermúdez understood by this work throughout the foundational processes he led; that is, from the creation of the school Colegio del Norte to the creation of the university Universidad de Pamplona. For this purpose, we will take up three points that build his idea about educating. First, we will question “What is educating for life”; second, we will analyze the perspective with which Faría understood the role of the student who asks questions with aplomb; and third, we hope to answer why we should study with love. This framed from a descriptive methodology that aims at a qualitative reconstruction of his thought from his main works.